(untitled) (Research, Society and Development, 2020)
The present study aimed to characterize the extruded sorghum flour (ESF) of the BRS 305 genotype (brown pericarp and tannin) in terms of physical-chemical, antioxidant and microbiological properties. For that, centesimal analyzes, quantification of the resistant, non-resistant and total starch contente were performed, as well as the evaluation of pH, antioxidant activity, absorption indexes in water, oil and milk and microbiological analyzes composed of more probable numbers of total coliforms and thermotolerant coliforms, mold and yeast count, Bacillus cereus and Salmonella spp. The flour evaluated presented moisture content (> 8%), with concentrations of proteins, lipids, ash and carbohydrates equal to 12.48%, 1.72%, 1.42% and 76.17%, respectively. Regarding the antioxidant activity by the ABTS method, the flour presented a content equal to 156.08 μmolTrolox.g-1. As for technological parameters, the absorption rates in water, oil and milk ranged from 1.35 to 2.34 g/g. In microbiological terms, all parameters evaluated were within the recommended standards. It is concluded that the ESF is suitable for human consumption, being an option of total or partial replacement of wheat flour, in bakery and/or confectionery products as it doesn’t contain gluten, thus being able to be consumed by individuals celiac or intolerant to this protein.